Quality of life of older adults admitted to a Medical Clinic Unit of a Public Hospital in Brazil - Núbia Pires da Rocha Martins; Salete Maria de Fátima Silqueira; Lívia Maria Emerick Souza; Carine de Paula Martins Souza; Sônia Maria Soares; Selme Silqueira Matos
Abstract Objective: To evaluate the quality of life of older adults admitted to the Medical Clinic Unit of a public hospital in Belo Horizonte, Brazil, to correlate the quality of life with the functionality proposed by the Katz index, and to characterize the clinical and epidemiological profile of the studied population. Method: This is a descriptive cross-sectional study with a quantitative approach. Data collection was performed through applying the Nottingham Health Profile instrument and the Katz Index instrument. Results: 116 older adults participated. The quality of life found in the study was considered good. It correlated with the Katz index (the more dependent, the worse the quality of life), the number of comorbidities (the higher the number of comorbidities, the worse the quality of life) and the family structure who lived with the older adults (there was worse quality of life for older adults who lived with their children). Conclusion: In this study it was found that the quality of life in the evaluated sample was good and that it is related to functionality, the number of comorbidities and with whom the older adult lives. Thus, poor quality of life cannot be associated with hospitalization in this sample.